PMO-043 Outcome of percutaneous endoscopic gastrostomy—how compliant we are with BSG guidelines?. (28th May 2012) - Ahmed, I; Belfield, K; Slim, D; Patel, R; Marden, P
Abstract : Introduction: Maintenance of enteral nutrition is considered to be beneficial for patients in whom the oral access has been lost. For long term tube feeding, PEG (percutaneous endoscopic gastrostomy) placement is of recognised advantage. A significant number of PEG tubes continue to be placed in patients for whom the benefits are questionable which account for significant procedure related morbidity and mortality. A better understanding of patient selection, designated multi-disciplinary framework and compliance with BSG guidelines are thought to improve outcome and minimise morbidity and mortality. Methods: We evaluated our practice of PEG tube placement against BSG guidelines in terms of patient selection, assessment, outcome and complications. It was a retrospective study. Medical record of patients who had PEG tube placement between February 2010 and March 2011 were studied. PEG related information was collected from endoscopy database and hospital electronic resources. Data were collected regarding pre-procedure clinical assessment, blood investigations, MRSA status, family involvement in decision making, underlying co-morbidities, post PEG care, early and late complications and 30 days mortality. Results: 52 patients aged 25–90 yrs (median age=78, F=28) were identified. 60% of the patients were assessed by a member of gastroenterology team prior to the procedure. Indications of PEG recorded were stroke (71%), pharyngeal cancer (10%), unsafe swallow (10%) and neurological condition (9%). Clotting was checked in 73% and MRSA status in 64% of cases. Family was involved in decision making in 73% of cases. 86% were reviewed by dietician pre or post procedure. 33% had early complications (within 1 week of the procedure, majority were pneumonia) while 12% had late complications (>1 week after PEG). 30 days mortality was 33% and 4% died within 2 days of the procedure. Overall compliance with BSG guidelines was unsatisfactory. Conclusion: PEG tube provides a durable access for enteral nutrition, whether or not it improves outcome, remains a matter of much debate. Guidelines have been developed by BSG to assist physicians in decision-making in order to minimise the morbidity and mortality associated with this procedure. A dedicated multi-disciplinary PEG team and better compliance with these guidelines would be an important strategy to improve outcome and minimise complications. Competing interests: None declared. References: 1. BSG Guidelines For Percutaneously Placed Entral Tubes . 2010. 2. NCEPOD. Scoping Our Practice . The 2004 Report Of The National Confidential Enquiry Into Patient Outcome And Death . London: NCEPOD, 2004.